Asymptomatic Aneurysms and HIV Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Aneurysms of major cerebral arteries in two children, aged 11 and 12 years, infected with human immunodeficiency virus from blood transfusions are reported from the National Institutes of Health, Bethesda, MD, and Georgetown University Hospital, Washington, DC.